The evolving role of ECMO in liver transplantation. Issue 3 (June 2021) - Hogen, Rachel; Sedra, Ashraf H.; Motamed, Arash; Emamaullee, Juliet
Abstract : Purpose of review: To review the indications for extra-corporeal membrane oxygenation (ECMO) in liver transplantation (LT) recipients and their optimal management on ECMO. Recent findings: Recent studies have reported a 30–40% survival rate among LT recipients that receive ECMO. Increasingly, case reports have documented successful outcomes of LT performed for patients on preoperative ECMO. Outcomes appear to be superior with patients in the immediate peri-LT period with reversible causes of severe, acute respiratory, and/or cardiovascular collapse. Mortality is most commonly secondary to infection. Volume optimization with CRRT may improve outcomes and perfusion to the graft, especially for patients on veno-arterial ECMO. There is little consensus on management of anticoagulation in these patients, but it can likely be held temporarily when the patient is coagulopathic and/or experiencing bleeding complications. Summary: ECMO should be considered in the peri-LT period for patients with severe, acute, and reversible causes of respiratory and/or cardiovascular collapse, with acceptable outcomes in patients that would otherwise not be expected to survive. Management of the post-LT patient on ECMO is challenging with a slowly enlarging body of literature to inform decision making.